IMPLEMENTASI PENDIDIKAN AGAMA ISLAM PADA ANAK YATIM PIATU DAN ANAK JALANAN - Mujiyati Mujiyati; Juli Amalia Nasucha (STAI Sangatta Kutai Timur, 2021)
This article aims to analyze and describe the implementation and implications of Islamic Religious Education (IRE) for orphans and street children at the Berkas Bersinar Abadi Lamongan foundation. This article uses qualitative research with a case study approach. The subjects in this study were the head of the foundation, members of the Islamic religious education supervisor, orphans and street children. The results showed that: (1) Islamic religious education for orphans and street children at the Berkas Bersinar Abadi Lamongan foundation was divided into three trainings; Akidah Education, Moral Education, and Moral Education, (2) the implementation of Islamic religious education for orphans and street children at the Berkas Bersinar Abadi Lamongan foundation which is applied to objects of development such as religious values ​​or religious values ​​with good morals or noble character, congregational prayers, recitations and several other forms of religious activities as exemplified by the Prophet Muhammad and his companions. (3) Positive implications; can interpret the two sentences of the Shahadah. Forming children's mental and character, and always being grateful for every gift He has given in this life.